25 Years of the Internet in Central America: an interview with Guy de Téramond - Siles González, Ignacio (2017)
January 2018 marks the 25th anniversary of the first dedicated Internet connection in Central America. Little is known about the conditions that characterised the early development of the Internet in this part of the globe. In this interview, made on 23 June 2017, Guy de Téramond, more commonly known as “The Father of the Internet in Central America”, recalls some of the main events that led the connection to BITNET and the Internet in this region. De Téramond talks about the motivations, challenges and satisfactions involved in regional connection projects in countries like Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua and Panama, during the 1990s; the role of the Organization of American States; the foundation of academic networks in Central America; and the privatisation of telecommunications in the region. These discussions are updated by addressing the contemporary state of these academic projects and some of the main challenges faced by countries of the Central American region in the global geopolitics and governance of the Internet.